Comparison of Interfacial Reactions Between AlSi7Mg and Alumina Filter After Casting and Spark Plasma Sintering**. Issue 12 (17th September 2013) - Salomon, Anton; Zienert, Tilo; Voigt, Claudia; Jäckel, Eva; Fabrichnaya, Olga; Rafaja, David; Aneziris, Christos G.; Aneziris, Christos G.
Abstract So‐called "small impingement tests" were performed with alumina ceramic foam filters and melt of the aluminum alloy AlSi7Mg (A356). A second set of samples was produced using the "spark plasma sintering" (SPS). After solidification, the resulting interface formation between metal melt and ceramic was compared to evaluate differences between the impingement test that is very close to industrial metal melt filtration conditions and the powder metallurgical SPS process without convection of the liquid metal. The melt generation and interface formation during SPS was characterized by high heating rates of up to 1500 K min−1, holding times of 1 min up to 60 min and fast cooling. Using energy and wavelength dispersive X‐ray spectroscopy, indications for spinel (MgAl2O4) were found at the original interface between AlSi7Mg melt and the alumina filter. Thermodynamic calculations were conducted and spinel formation was confirmed. It was demonstrated that SPS could serve as a fast and reliable tool to facilitate the reactions that occur at metal melt/ceramic interfaces during filtration.